Use of Capstone Experiences in Pharmacy Education to Synthesize and Apply Students’ Knowledge and Skills - Minshew, Lana M. (Am J Pharm Educ, 2020)
Objective. To investigate capstone experiences in pharmacy education with the broad aim of better understanding how they are designed, used, and sustained. Methods. Capstones were defined as culminating experiences that required Doctor of Pharmacy (PharmD) students to apply their knowledge and skills and demonstrate their ability to integrate, extend, and apply multiple components of their academic experience. This study was conducted in two phases. Phase one was a mapping review, which provided insight into the design of pharmacy capstone experiences, including the purpose they served and their associated outcomes. Phase two consisted of conducting follow-up interviews to explore the current status and sustainability of those capstone experiences. Qualitative methods with multiple coders were used to analyze the data. Results. Five distinct purposes for capstone experiences were identified: preparation for advanced pharmacy practice experiences (APPEs), pharmacotherapy education, research, reflection on pharmacy school experiences, and immersive learning through an external organization. Wide variability was found in the design, purpose, and outcomes of capstone experiences. Study authors described the capstone experiences at their institution in terms of the viability, feasibility, desirability, and challenges faced. Conclusion. Capstones can play an important role in assessing student progress and practice readiness in pharmacy education. The findings of this study can be used to help pharmacy schools design capstone experiences that are effective and sustainable.